Difficulties of information seeking in using university library and solving ways -A field study at Tishreen University- - ALI, Khodor; nameh, Rasha (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aims at determining the degree of the difficulties of the information seeking by using university library in the areas of: ( sources group, technician procedures, time, place, dealing with employees), To achieve the objectives of the research, the researcher used descriptive approach, a questionnaire was done . consisting of (20) clause. It was distributed for (544) students in Tishreen University at 2015/2016. , and relying on appropriate statistical methods, results were as following: 1- This research resulted in a medium degree of the difficulties of the information seeking by using university library in the field of sources group because of lack of academic specialist sources. 2- This research resulted in a medium degree of the difficulties of the information seeking by using university library in the field of technician procedures because university library depends on classification in general not specialist one. 3- This research resulted in a medium degree of the difficulties of the information seeking by using university library in the field of time because time sometimes is suitable for students according to lectures table, sometimes is not. 4- This research resulted in a medium degree of the difficulties of the information seeking by using university library in the field of place because of some chaos. 5- This research resulted in a medium degree of the difficulties of the information seeking by using university library in the field of dealing with employees because of lace of librarian and specialist employees too. 6- the difficulties of information seeking increase throughout the coming years of studying because of student in high studies degree search for information more than student in license degree. 7- Students suggest some ways that decrease difficulties of information seeking in using university library: ( acquire specialist sources, depend specialist classification, increase hours that students can use the library, attention of library's furniture, appointment specialist employees at faculty field, increase copies of required books, design system of university library's data on internet)